(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Background: The most crucial and commonly asked question in medicolegal investigations is determination of postmortem interval (PMI). The calculation of PMI has been widely studied by forensic scientists around the globe in the past and many advanced methods are now being practiced. The following review summarizes the attempts made in forensic medicine by Indian forensic scholars to pinpoint the PMI using molecular biology methods, entomological based methods, thanatochemistry and other methods such as histological assessment of cellular changes, enzyme activity and rigor mortis. Methodology: Studies on postmortem interval by Indian forensic scholars were retrieved through a systematized internet search of the databases “MEDLINE”; “EMBASE”; “ScienceDirect”; “Scopus”; “PubMed”; and “Google Scholar” using the keywords time since death, forensic medicine, postmortem interval, PMI, forensic science, proteins, RNA, forensic entomology, thanatochemistry, vitreous humor, synovial fluid, cerebrospinal fluid, and India, with the last search accomplished in July, 2020.